Three new species of Glossobalanus (Hemichordata: Enteropneusta: Ptychoderidae) from western North America - Cameron, Christopher B.; Ostiguy, Angélica (Zootaxa, 2013)
Twenty three enteropneust species have been described from the west coast of North America, including one species from the family Ptychoderidae, Glossobalanus berkeleyi from the Salish Sea, Vancouver Island. Here we use morphology to describe three additional species of acorn worms in the genus Glossobalanus: G. williami from Cape Arago, Oregon; G. hartmanae and G. barnharti fromLa Jolla,California. Notes on the habit and localization of each species as well as a dichotomous key to the genera of the family Ptychoderidae are provided.